FALSE CONSCIOUSNESS IN IMBOLO MBUE’S BEHOL THE DREAMERS - Moch. Syaiful Anwar (Metalanguage: Jurnal Ilmu Bahasa dan Sastra Indonesia, 2021)
ABSTRACT: The research which entitled as False Consciousness in Imbolo Mbue’s Behold the Dreamers reports a study of false consciousness found in two main characters. The data are taken from the characters in the novel who pursue their dreams in America as an immigrant. This research aims to find how the characters’ false consciousness depicted in the novel. The method used in this research is descriptive qualitative. This research finds the false consciousness depicted toward the characters in pursuing American dream. The research shows that false consciousness is experienced by the two immigrants to achieve their dreams in America but they are failed to gain material wealth since their belief appears only to have a power to compete others’ point of view about their class structure.